THE IMPACT OF IMPLEMENTING DEEP LEARNING ON STRENGTHENING ISLAMIC RELIGIOUS EDUCATION VALUES - Nurgenti, Sheilda (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
This study analyzes the implementation of deep learning at SMP IT Ishlahul Ummah Prabumulih, a private school in Prabumulih that has adopted this approach. The research employs a descriptive qualitative method with data collection techniques including observation, interviews, and document analysis. The data are presented in narrative form and tables. The findings indicate that deep learning is integrated into both religious and general subjects and is reinforced through school programs and various student activities. The impact of implementing deep learning includes increased motivation for worship, improved focus during the learning process, and active student participation in class. The learning model that synergizes formal and non-formal education has proven effective in strengthening Islamic Education values. The values developed include manners (adab), mutual respect, responsibility, and noble character (akhlaq). The practical implication of this study is that the implementation of deep learning can be replicated in other Islamic schools with contextual adjustments according to local needs.